Development of flood disaster preparedness activity (FDPA) items: a preliminary study using Rasch analysis - Hashim, Hajar Mariah; Ng, Yee Guan; Talib, Othman; Mohd Tamrin, Shamsul Bahri (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Not only does flood affects the household community, but it also has an impact on business entities, particularly small and medium enterprises (SMEs) located in flood-prone areas. In order to assist SMEs to prepare for a flood disaster effectively, the set-up of a disaster preparedness plan is essential. The purpose of this study is to develop a validated instrument for identifying the different levels of disaster preparedness among SMEs in their readiness to face a flood disaster. Methods: In this preliminary study, 26 items of flood disaster preparedness activities (FDPA) reviewed from works of literature were adopted and adapted to be randomly administered to 30 respondents (SME business owners) located in the Temerloh province, Malaysia, which is identified as a flood-prone area. A Rasch analysis technique was used to identify the psychometric properties of the instrument. Results: Using the Rasch measurement analysis technique, the instrument used was able to categorise the SMEs into two level of preparedness: low and moderate. About 25 items were found to possess good psychometric features in determining the flood preparedness level of SMEs despite the lack of items on measuring high-level preparedness activities. Conclusion: The results of this preliminary study have served to highlight the strength of the instrument and gaps identified for further improvement in the near future.